2007
DOI: 10.1002/jmri.20931
|View full text |Cite
|
Sign up to set email alerts
|

Soft‐tissue tumors evaluated by line‐scan diffusion‐weighted imaging: Influence of myxoid matrix on the apparent diffusion coefficient

Abstract: Purpose To compare the apparent diffusion coefficients (ADCs) of myxoid and nonmyxoid soft‐tissue tumors using line‐scan diffusion‐weighted imaging (LSDWI), and to investigate the myxoid matrix influence on ADCs of soft‐tissue tumors. Materials and Methods This study enrolled 44 patients with soft tissue tumors. They were divided into two groups: one with myxoid‐containing soft‐tissue tumors (N = 23) and the other with nonmyxoid soft‐tissue tumors (N = 21). The 44 patients were also classified histologically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 17 publications
11
75
0
5
Order By: Relevance
“…To date, no study has reported the features of odontogenic myxomas on DWI. The myxoid matrix is peculiar in that free water is abundant in extracellular spaces [13]. This explains our findings of free diffusion and high ADC values (2.091¡0.19610 23 mm 2 s 21 ) in these lesions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To date, no study has reported the features of odontogenic myxomas on DWI. The myxoid matrix is peculiar in that free water is abundant in extracellular spaces [13]. This explains our findings of free diffusion and high ADC values (2.091¡0.19610 23 mm 2 s 21 ) in these lesions.…”
Section: Discussionsupporting
confidence: 62%
“…This explains our findings of free diffusion and high ADC values (2.091¡0.19610 23 mm 2 s 21 ) in these lesions. The study by Maeda et al [13] on musculoskeletal and soft-tissue tumours also showed that myxoid tumours have high ADC values when compared with non-myxoid tumours. Thus DWI may provide an additional paradigm to distinguish odontogenic myxoma from KCOT.…”
Section: Discussionmentioning
confidence: 91%
“…The results in these 3 cases were similar to those of previous reports, 12,13,22 but the remaining case, a myxoid leiomyosarcoma, showed a high ADC value due to the myxoid component. Maeda and associates 23 reported significantly higher ADC values of myxoid-containing soft-tissue tumors than nonmyxoid soft-tissue tumors; furthermore, the myxoid matrix influenced the ADC values of both benign and malignant tumors. Tamai's team 22 reported the high SI of uterine sarcomas and cellular leiomyomas on DW images.…”
Section: Discussionmentioning
confidence: 95%
“…There have been inconsistent reports [8][9][10][11][12][13][14] using diffusion-weighted imaging (DWI) at 1.5 T for differentiation of malignant from benign soft tissue tumours. Benign lesions such as lipoma, epidermal inclusion cyst, and localized tenosynovial giant cell tumour (giant cell tumour of tendon sheath) can have low apparent diffusion coefficients (ADCs), while malignant tumours with myxoid or chondroid components have high ADCs [10,11,15]. However, the diagnosis can be easily made based on standard MRI in most cases of lipoma, epidermal inclusion cyst, and localized tenosynovial giant cell tumour.…”
Section: Introductionmentioning
confidence: 99%